How to Construct a University Study Program Based Upon the Learning Paradigm? - Stražinskaitė, Dalia (Pedagogika, 2014)
The article deals with mechanisms of high school education program construction in terms of learning paradigm in social, epistemological and technological points of view. In undergraduate education the concept of learning paradigm refers to the constructivist approach to learning as a process and to student empowerment process. A study program is defied as a written form of curriculum. In social terms, strategic and political expectations of various interest groups: the academic community, the state and the market are reflected by the objectives and goals of program. In the model of the learning paradigm we must include the learner as a customer and a manager of his own learning process. Meanwhile, the social constructs (public institutions of accreditation; over evaluation of the market approach; the elite academic community) does not dare to transfer their responsibility. In epistemological point of view, the modularization provides flexibility of the program and procedural approach to program construction. However, curriculum content should not be focused only on knowing and acting (competencies required for the market), but also on being − a value for students personal development. Taking in account H. Gardner’s multiple intelligences theory, a study program has to integrate variations in learning styles. Besides, the additional resources must be provided to create rich educational environments and new assessment mechanisms before and after the learning process.